(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
An analysis of the definition of the concept of "physical recreation" was carried out. The limits of the use of the studied concept and the main features that reflect it have been established. The content aspect of physical recreation, which is recommended for its implementation, has been studied. The inconsistency of the used means with the main definitive signs was revealed. The main risks for health during the use of inadequate means of physical recreation are noted. The problem of the research is that there are excessive ideas about the content of physical recreation, which makes it difficult to achieve its main goal - the restoration of the vital forces of any person. In order to achieve the goal of this study, the scientific works of Ukrainian scientists dealing with the problems of physical recreation and foreign specialists in the field of health-related physical culture were studied. In order to achieve the goal of this study, the scientific works of Ukrainian scientists dealing with the problems of physical recreation and foreign specialists in the field of health-related physical culture were studied. With the help of contextual analysis, the main features and target settings that determine the content of recreational activities are highlighted. The results of the analysis of the definition of the concept of "physical recreation" and the problems that arise due to the ambiguity of its interpretation when choosing the content of recreational activities are given. It is noted that the increasing tension of modern life simultaneously increases the level of the total load that a person receives in the course of daily life, and worsens his health. Scientists have researched that it is physical recreation that ensures the restoration of the body’s vital forces and their support in the process of daily life. The factors of inclusion in the content of recreational forms of classes of various types of physical exercises are defined and substantiated.